Innovations in Energy Conversion Systems: A Mechanical Engineering Perspective - Singh , Gourav (Journal of Advanced Research in Mechanical Engineering and Technology, 2024)
The pursuit of efficient, sustainable, and versatile energy conversion systems is essential for addressing the challenges of climate change, resource depletion, and energy security. In this article, we explore the latest innovations in energy conversion systems from a mechanical engineering perspective. From renewable energy technologies to combustion engines, electrification, thermoelectric generators, and system integration, we delve into cutting-edge advancements reshaping the landscape of energy production, distribution, and utilization. With a focus on integration and optimization strategies, including model-based design, multi-objective optimization, data-driven analytics, energy storage management, hybridization, and lifecycle analysis, we highlight the pivotal role of mechanical engineers in driving progress towards a cleaner, more sustainable energy future. Through collaborative efforts and interdisciplinary research, we envision a future where energy conversion systems seamlessly integrate diverse technologies and energy sources, maximizing performance, efficiency, and environmental sustainability.